Utilization of Institutional Maternal Delivery and Associated Factors among Rural Women: A Case Study of High Priority District of Himachal Pradesh - Mandeep Kaur (Indian Journal of Public Health)
Background: Utilization of institutional maternal delivery is the cornerstone for the health of both mother and child which provides essential emergency care and reduces the risk of maternal and neonatal mortality. The aim of the current study is to analyze the perceptions of pregnant women regarding the place of maternal delivery in Lahaul and Spiti. Materials and Methods: A cross-section study was conducted among 410 pregnant women in remote district of Himachal Pradesh. Data collection was done by multistage random sampling through an interview method using a structured questionnaire. Descriptive statistics, principal component analysis, and logistic regression were applied to find out the outcomes. Results: Out of 410 study participants, 230 women had perception for utilizing the institutional maternal delivery and 180 had perception to utilize home delivery. More than 80% of women who preferred institutional birth had high severity for medical complications and preterm birth threat. The women who attended more than 4 antenatal care (ANC) visits had 2.86 more chances to go for hospital birth (confidence interval [CI] = 0.41–4.23, P < 0.05). The odds of women who believed in high perceived threat in home delivery had 1.99 more chances to go for institutional maternal delivery. Conclusion: The study highlights that public maternal health policies in the remote areas are to increase the proportion of utilization of institutional maternal deliveries. The policy imperative for remote villages requires to upgrade the weak health infrastructure and boost ANC and transportation facilities for better implementation of government maternity healthcare schemes.